The Influence of Corporate Social Responsibility toward the Financial Performance Company in Jakarta Islamic Index (JII) in Period 2010-2014 - P. Prasojo; Inon Listyorini (Global Review of Islamic Economics and Business, 2015)
The aim of this research is to examine the influence of corporate sosical responsibility (CSR) toward the financial performance that is measured by Return on Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS),  Firm's Growth (FG) and the control variable of Siz, Leverage, and Age. The population in this research was the companies in Jakarta Islamic Index (JII) consistently from 2010-2014. The samples were selected by Purposive Judgment sampling criteria. The collected samples in this research were 11 companies. The result of CSR research has a significant on financial performance by proxy ROA, ROE, EPS, and FG.